Pengaruh Terapi Suportif Kelompok terhadap Kecemasan pada Klien Pasca Bencana Banjir Bandang di Perumahan Relokasi Desa Suci Kecamatan Panti Kabupaten Jember (The Effect of Supportive Group Therapy toward the Client’s Anxiety after Flash Flood Disaster - Fitri Nurcahyani; Erti Ikhtiarini Dewi; Rondhianto Rondhianto (Pustaka Kesehatan, 2016)
Anxiety as psychosocial problems were emerged as stimulated by stress after flash flood disaster. Supportive group therapy is an effective method to solve some psychosocial problems. This research was intended to analyze the effect of supportive group therapy toward the client’s anxiety after flash flood disaster at relocation housing in Suci Village. The research used quasi-experimental non equivalent with control group design with 36 respondents divided into 2 groups: 13 respondents in intervention group, and 23 respondents in control group. Data were analyzed by using paired t-test and Independent t-test with 95% of CI. The research showed that p value of paired t-test in experimental group is 0,000 and 0,004 in control group, while p value of independent t-test was 0,000 (p